Ten‐year prevalence of acute hospital ENT infections and the impact of COVID: A large population study. (17th September 2022) - Mettias, Bassem; Jenkins, David; Rea, Peter
Abstract: Background: Acute ear, nose and throat (ENT) infections were the commonest referrals from accident and emergency to ENT services. The referral rate changed dramatically with season, year, national outbreaks and during the COVID pandemic. Method: Retrospective longitudinal study of the epidemiology of seven acute ENT infections in secondary care over 10 years. A mixed city and rural population of over 650 000 in central England was studied. The risk factors for each wave of infection during the surge of infection were sought. A statistical analysis of their significance was undertaken. This included analysis and correlation of group A‐beta haemolytic streptococcus (GABHS) in hospital and community. Seasonal variations, hospital admissions and the impact of the COVID were analysed. Results: There were 16 883 reported cases of the seven index ENT infections during the 10‐year period. Great seasonal and year‐to‐year variations were recorded. There was an incremental rise in 2018. Spring had the highest season of acute ENT infections. An outbreak of GABHS was noted in the community in 2014. The mean duration of hospital admission was 1.5 days. There was no statistical ethnic or gender predominance. A dramatically lower number of acute ENT infections were recorded during the COVID‐19 pandemic, and this continued after lifting of lockdown restrictions. Conclusion: A resurgence in scarlet fever directly and indirectly contributed to an incremental rise in acute ENT infections in the following years. Both hospital and community B‐haemolytic cultures have declined during the COVID‐19 pandemic due to a reduction in infections as opposed to reduced case ascertainment.